Capital structure, efficiency, and profitability: key drivers of Islamic banking’s financial stability in ASEAN - Pungky Lela Saputri; Hanif Ahmadi; Tika Mutiani (University of Darussalam Gontor, 2025)
This study examines the impact of capital structure, operational efficiency, and profitability on the financial stability of Islamic banks in ASEAN from 2020 to 2024. Using panel data regression analysis, the research investigates how the Debt to Equity Ratio (DER), Operational Efficiency Ratio (OER), and Return on Assets (ROA) influence financial stability, measured by the Z-Score. The findings reveal that DER has a negative and significant effect on financial stability, indicating that excessive reliance on debt increases financial risk and reduces the resilience of Islamic banks. Similarly, OER negatively affects financial stability, suggesting that higher operational costs and inefficiencies weaken financial performance. In contrast, ROA positively and significantly contributes to financial stability, as higher profitability strengthens banks’ financial flexibility and ability to absorb economic shocks. These results highlight the importance of maintaining an optimal capital structure, improving cost efficiency, and enhancing profitability to ensure sustainable financial stability. The study provides practical implications for policymakers and Islamic bank managers, emphasizing the need for prudent financial management, technological advancements in cost control, and innovative Shariah-compliant investment strategies to enhance stability in the Islamic banking sector.